Expression levels of complement regulatory proteins (CD35, CD55 and CD59) on peripheral blood cells of patients with chronic kidney disease - Eldewi DM; Alhabibi AM; El Sayed HME; Mahmoud SAK; El Sadek SM; Gouda RM; Hassan MAEM; Ibrahim AH; Abd El Haliem NF (International Journal of General Medicine, 2019)
Dalia Mahmoud Eldewi,1 Alshaymaa M Alhabibi,1 Hanaa Mohammed Eid El Sayed,2 Sammar Ahmed Kasim Mahmoud,2 Sanaa Mohammed El Sadek,3 Rasha Mahmoud Gouda,3 Mohammed Abd El Malik Hassan,4 Amal H Ibrahim,2 Naglaa F Abd El Haliem5 1Clinical Pathology Department, Faculty of Medicine for Girls, Al-Azhar University, Cairo, Egypt; 2Internal Medicine Department, Faculty of Medicine for Girls, Al-Azhar University, Cairo, Egypt; 3Pediatric Department, Faculty of Medicine for Girls, Al-Azhar University, Cairo, Egypt; 4Pediatric Department, Faculty of Medicine for Boys, Al-Azhar University, Cairo, Egypt; 5Medical Microbiology and Immunology Department, Faculty of Medicine for Girls, Al-Azhar University, Cairo, EgyptCorrespondence: Alshaymaa M AlhabibiClinical Pathology Department, Faculty of Medicine for Girls, Al-Azhar University, Cairo 11765, EgyptTel +20 100 289 4075Email Elshymaamohamed.medg@azhar.edu.egBackground: Altered regulation of the complement system is associated with multiple kidney diseases. CD35, CD55 and CD59 regulate the complement system, and changes in their expression have previously been linked with kidney disease. This study assessed whether changes in the expression levels of these proteins are associated specifically with chronic kidney disease (CKD) to understand its pathogenesis.Materials and methods: Sixty CKD patients and 60 age-matched controls were enrolled and divided into two groups: Group I (n=30 pediatric patients and n=30 controls) and Group II (n=30 adult patients and n=30 controls). The expression of CD35, CD55 and CD59 on peripheral blood cells was evaluated by flow cytometry as the proportion of positive cells expressing the marker and mean fluorescence intensity (MFI), also the relation of these markers to the stage of CKD was also evaluated.Results: Pediatric and adult CKD patients had significantly lower proportion of erythrocytes expressing CD35, CD55 and CD59 than healthy controls (P<0.001). In pediatric CKD patients, there was no significant difference in the three studied markers on neutrophils, lymphocytes and monocytes. The changes in expression of CD35, CD55 and CD59 on leukocytes were more pronounced in adult patients, who had lower proportion of CD59-positive neutrophils, CD35- and CD59-positive lymphocytes, and CD59-positive monocytes, as well as lower expression of CD59 on neutrophils and monocytes than adult controls (P<0.001, P=0.019, P<0.001, P=0.026, P<0.001 and P=0.003, respectively). The eGFR directly correlated with the proportion of positivity of some of those markers on peripheral leukocytes while there was inverse correlation between the disease stage and the same markers.Conclusion: There are alterations in the patterns of expression of complement regulatory proteins CD35, CD55 and CD59 on peripheral blood cells of patients with CKD compared with healthy controls.Keywords: complement regulatory proteins, CD35, CD55, CD59, chronic kidney disease